Experimental study of the performance of Al2O3/water nanofluid in condensing unit of air conditioner. (2020) - Manirathnam, A.S.; Senthil Kumar, K.; Prabhu, R.; Sivashankar, M.; Hariharan, N.
Abstract: In the present investigation, nano fluids contains suspension of nanoparticles (Al2 O3 ) in water (base fluid) with different concentrations (1%, 2%, 3% and 4% by volume) are produced. Nano fluids taken as a cold fluid in the condensing unit of air conditioner and the heat transfer rate has investigated. Experimental results emphasis the enhancement of heat transfer rate by 1.77–37.35% due to the nanoparticles presence in the cold fluid. Coefficient of heat transfer is increases with increase in volume concentration of nanoparticles in the base fluid.